ANALYSIS OF CONSUMER PREFERENCES GEN Z IN PURCHASING DOUGHNUTS USING THE CONJOIN METHOD - Rahayu, Nastiti Putri; Sienatra, Krismi Budi (Parsimonia - Jurnal Ekonomi dan Bisnis, 2025)
This research aims to identify consumer preferences for product attributes, which can be leveraged for business development and marketing strategy planning. The study employs a quantitative approach using conjoint analysis. Sixteen stimuli were tested, derived from an orthogonal design, based on five key attributes: (1) Topping, (2) Filling, (3) Size, (4) Packaging, and (5) Price. The findings reveal that consumers prefer donuts with fresh fruit toppings and rich chocolate fillings. A 9 cm donut size is the most favored, as it offers a sense of adequacy and satisfaction. Mica box packaging is perceived as more premium and practical, while a price range of IDR 17,000 – IDR 22,000 is considered reasonable for the quality provided. Beyond taste, consumers highly value visual appeal and product convenience, including packaging design and size. These results provide strategic insights to prioritize product development that emphasizes quality, flavor innovation, and appealing designs. By aligning product attributes with consumer preferences, businesses can strengthen customer loyalty and expand their market share.